2012
DOI: 10.1103/physrevlett.109.096803
|View full text |Cite
|
Sign up to set email alerts
|

Giant Ambipolar Rashba Effect in the Semiconductor BiTeI

Abstract: We observe a giant spin-orbit splitting in bulk and surface states of the non-centrosymmetric semiconductor BiTeI. We show that the Fermi level can be placed in the valence or in the conduction band by controlling the surface termination. In both cases it intersects spin-polarized bands, in the corresponding surface depletion and accumulation layers. The momentum splitting of these bands is not affected by adsorbate-induced changes in the surface potential. These findings demonstrate that two properties crucia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

21
222
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 177 publications
(244 citation statements)
references
References 28 publications
21
222
1
Order By: Relevance
“…1 and 6, which assign it to a bulk conduction branch and agrees within 50% with the values from Ref. 8, but for electronic bands assigned to the surface. Moreover, it also agrees within better than 50% with the value of k F for the surface states near the bottom of the conduction band, obtained from band structure calculations 9 .…”
supporting
confidence: 75%
See 1 more Smart Citation
“…1 and 6, which assign it to a bulk conduction branch and agrees within 50% with the values from Ref. 8, but for electronic bands assigned to the surface. Moreover, it also agrees within better than 50% with the value of k F for the surface states near the bottom of the conduction band, obtained from band structure calculations 9 .…”
supporting
confidence: 75%
“…Optical spectroscopy of this compound found indeed an electronic excitation spectrum consistent with the splitting of the bulk conduction and valence bands 5 and further photoemission study suggested the 3D nature of these bands 6 . More recent ARPES reports however, indicated the reconstruction of the band structure at the Te (or I) terminated surface and the existence of surface electronic branches, possibly with even larger Rashba spinsplitting 7,8 . On the theoretical side, ab-initio calculations for BiTeX(X=Cl, Br, I) do claim the formation of a surface 2D electron system distinct from the bulk states that has a larger Rashba splitting 9 .…”
mentioning
confidence: 99%
“…An additional state, b2, disperses between the two. It is hardly detectable at this photon energy and we attribute it to the outer branch of the three-dimensional bulk-derived spin-split state [9,11]. Fig.…”
mentioning
confidence: 99%
“…In the case of BiTeI, the unit cell is formed by the alternation of Bi, Te, and I layers, with P 3m1 point group symmetry. The natural cleavage plane is between Te and I and both terminations are possible [9,37]. In this study we focus only on the electronic properties of the Te-terminated surfaces of all the compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation